?- Wijsman statistical convergence on time scales - Yilmaz, Emrah; Gulsen, Tuba; Altin, Yavuz; Koyunbakan, Hikmet (Taylor & Francis Inc, 2023)
We construct lambda- Wijsman density and lambda- Wijsman statistical convergence (SC) on a time scale. Furthermore, strongly Wijsman lambda(p) - summability is defined. Also, inclusion relations for sets of Wijsman statistical convergent sequences are given by considering the sequences mu(Delta lambda(t)) and mu(Delta beta(t)) in the class Lambda on time scales. These theoretical parts are supported by some results and examples.
Keywords: Summability; time scales; statistical convergence